The Use of English Song for Improving Students' Vocabulary Mastery: Action Research - Wirdayarti, Nanda; Istiara, Febriyantina; Sutiyono, Akhmad (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2022)
The goal of this study was to promote students' vocabulary mastery using English song at MTs Negeri 2 Bandar Lampung's eighth grade. The thirty-two participants in this study were made up of 11 males and 19 females. This study was carried out with the use of classroom action research. The action research model, according to Kemmis and Taggart, consists of two cycles. Planning, action, observation, and reflection were the four steps in each cycle. Before beginning cycle 1, the writer conducted a pre-cycle to determine the students' vocabulary competence as well as their vocabulary challenges. In this study, the writer worked with an English teacher at MTs Negeri 2 Bandar Lampung to collect data from students in the eighth (VIII C) grade. The writer's goal for this study was to increase the students' learning activities and vocabulary knowledge. The students' improvement in learning activities was evident from the average score of students' learning activities in cycle 1 of 7.16 with the criteria quite active, while in cycle 2 of 7.83 with the criteria quite active. As a result, there was a 0.67 point improvement in students' learning activity between cycles 1 and 2. Meanwhile, the students' vocabulary mastery improved, as seen by the average pre-cycle score of 66.25, with 12 students passing the Minimum Mastery Criterion. The average score for the first cycle was 70.87, with 13 students 40.62% passing the Minimum Mastery Criterion, while the average score for the second cycle was 81.37, with 26 students 81.37% passing the Minimum Mastery Criterion. Based on the findings of the data analysis, it is possible to conclude that Classroom Action Research using English song can promote students' learning activities and vocabulary acquisition.